2003
DOI: 10.1097/01.ju.0000077558.48257.3d
|View full text |Cite
|
Sign up to set email alerts
|

The Nonsteroidal Effects of Diethylstilbestrol: The Rationale for Androgen Deprivation Therapy Without Estrogen Deprivation in the Treatment of Prostate Cancer

Abstract: The efficacy of 1 mg DES extends well beyond its androgen suppressive effects. Androgen deprivation without estrogen deprivation is a concept that deserves further attention in the urological community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0
6

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 63 publications
0
39
0
6
Order By: Relevance
“…It is well known that castration and treatment with diethylstilbestrol (DES) result in significant decreases in circulating concentrations of testosterone and DHT (34). To minimize the competitive binding from endogenous androgen, we further compared the biodistribution of 125 I-labeled S-26 in intact rats to that observed in castrated rats and intact rats treated with DES in an attempt to clarify the role of AR mediated uptake in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that castration and treatment with diethylstilbestrol (DES) result in significant decreases in circulating concentrations of testosterone and DHT (34). To minimize the competitive binding from endogenous androgen, we further compared the biodistribution of 125 I-labeled S-26 in intact rats to that observed in castrated rats and intact rats treated with DES in an attempt to clarify the role of AR mediated uptake in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical use has been restricted owing to its adverse side effects, which mainly involve increased heart-vascular complications. Recently, interest in the use of estrogenic therapies for advanced prostate cancer has reemerged, since lower doses of estrogen have proven effective in subpopulations of patients with advanced prostate cancer (5,22,23). Additionally, the administration of estrogens parenterally, which avoids hepatic first-pass metabolism, appears to lower the risk of thromboembolism (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Several trials demonstrated a persistence of DES efficiency after a first-line hormonal therapy failure. [2][3][4][5][6][7][8] It has been reported that prostate-specific antigen (PSA) levels decreased by more than half in 21%-86% of patients treated with DES. However, its side effects (e.g., thrombosis and cardiac toxicity) have hindered its use; even at a low dose (1 mg), toxicity was observed in almost 20% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, its side effects (e.g., thrombosis and cardiac toxicity) have hindered its use; even at a low dose (1 mg), toxicity was observed in almost 20% of patients. [2][3][4][5][6][7][8][9] Several mechanisms for its action have been suggested, including the inhibition of the hypothalamo-pituitary axis by negative biofeedback, direct testosterone production inhibition by the testis and adrenal glands, and direct cytotoxicity on prostatic cancer cells. This direct effect mechanism is unknown, and identification of the responsible proteins may lead to the development of targeted therapies.…”
Section: Introductionmentioning
confidence: 99%